2020
DOI: 10.3390/sym12071106
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Mistaking Enantiomers for Different Compounds Due to the Self-Induced Diastereomeric Anisochronism (SIDA) Phenomenon

Abstract: The NMR phenomenon of self-induced diastereomeric anisochronism (SIDA) was observed with an alcohol and an ester. The alcohol exhibited large concentration-dependent chemical shifts (δ’s), which initially led us to erroneously consider whether two enantiomers were in fact atropisomers. This highlights a potential complication for the analysis of chiral compounds due to SIDA, namely the misidentification of enantiomers. A heterochiral association preference for the alcohol in CDCl3 was determined by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Therefore, whether compounds are crystalline or liquid, of low or high molecular weight, polar or non-polar, etc., they are likely to be amenable to chromatography. Notably, SDEvC has been observed for all manner of chromatographic techniques, such as high-pressure liquid chromatography (HPLC) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], medium-pressure liquid chromatography (MPLC) [ 18 , 19 , 20 , 21 ], routine, gravity-driven column chromatography [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], flash chromatography [ 35 , 38 , 39 , 40 ], preparative thin-layer chromatography (PTLC) [ 10 , 41 ], and size-exclusion chromatography [ 42 , 43 ], as well as under a variety of conditions such as normal- and reverse-phase conditions and for various stationary phases [ 37 , 38 ]. Some noteworthy theoretical studies [ 15 , 73 , 74 , 75 , 76 , 77 ] have been conducted on SDEvC to describe the process.…”
Section: Preview Of the Sdementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, whether compounds are crystalline or liquid, of low or high molecular weight, polar or non-polar, etc., they are likely to be amenable to chromatography. Notably, SDEvC has been observed for all manner of chromatographic techniques, such as high-pressure liquid chromatography (HPLC) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], medium-pressure liquid chromatography (MPLC) [ 18 , 19 , 20 , 21 ], routine, gravity-driven column chromatography [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], flash chromatography [ 35 , 38 , 39 , 40 ], preparative thin-layer chromatography (PTLC) [ 10 , 41 ], and size-exclusion chromatography [ 42 , 43 ], as well as under a variety of conditions such as normal- and reverse-phase conditions and for various stationary phases [ 37 , 38 ]. Some noteworthy theoretical studies [ 15 , 73 , 74 , 75 , 76 , 77 ] have been conducted on SDEvC to describe the process.…”
Section: Preview Of the Sdementioning
confidence: 99%
“…Over the last decade, systematic research into the phenomenon of the self-disproportionation of enantiomers (SDE) [ 5 , 6 , 7 , 8 , 9 , 10 ] has clearly revealed that the accuracy in reporting the stereochemical outcome of enantioselective reactions represents a major issue of concern in terms of data integrity and the understanding of the stereochemical mechanisms at play and the interpretation of the results. It has been unequivocally shown that any physicochemical treatment, including achiral chromatography [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] or even rotary evaporation [ 40 , 44 ], of a scalemic sample inevitably leads to fractionation of the material into portions of variable enantiomeric excess (ee), with consequent erroneous reporting of the stereochemical outcome if due care is not taken. Yet, there is a deficiency in the general understanding and appreciation of the SDE phenomenon, even though it has been known for a considerable length of time now.…”
Section: Introductionmentioning
confidence: 99%
“…Because the formation constant for the association of homochiral molecules (K hom ), i.e., R with R or S with S, is likely to be different to the formation constant for the association of heterochiral molecules (K het ), the positions of the two equilibria will likely be different. Therefore, the observed δ of a nucleus is the population-weighted average of the δ's of the nucleus in the three states SM, HOM, and HET [1][2][3]. Furthermore, as the equilibrium shifts with a change in conditions (e.g., concentration or temperature), the contributions of the δ's from the SM, HOM, and HET states to the population-weighted average δ alter accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as the equilibrium shifts with a change in conditions (e.g., concentration or temperature), the contributions of the δ's from the SM, HOM, and HET states to the population-weighted average δ alter accordingly. Enantiopure and racemic solutions can exhibit distinct spectra because of these dynamic effects, and even distinct signals for the two enantiomers can result in the case of scalemates [1,3,4]. The SIDA phenomenon with many fine examples in the literature [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] has been well reviewed in the past [1,19] and theoretically explained [3,20] along with its potential applications and problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation